Curcuma pulcherrima (Zingiberaceae), a new rare species of Curcuma subgen. Ecomata from eastern Thailand - PIYAPORN SAENSOUK; THAWATPHONG BOONMA; SURAPON SAENSOUK (Society for Indonesian Biodiversity, 2022)
Abstract. Saensouk P, Boonma T, Saensouk S. 2022. Curcuma pulcherrima (Zingiberaceae), a new rare species of Curcuma subgen. Ecomata from eastern Thailand. Biodiversitas 23: 6635-6644. Curcuma pulcherrima Boonma, Saensouk & P. Saensouk sp. nov. (Zingiberaceae: Zingibereae, belonging to Curcuma subgenus Ecomata) distributed in Ubon Ratchathani Province, the eastern part of Thailand. The morphological characteristic of this species causes it to fall into Curcuma subgenus Ecomata due to the presence of epigynous glands, lack of coma bracts, bracts fused only at the base, and production of open-form flowers. Furthermore, this species is similar to Curcuma pierreana Gagnep., due to its similar color flowers with a pink tinge, but lighter (vs. C. pierreana maroon tip), and similar to Curcuma siamensis Saensouk & Boonma due to its characteristics of the anther and spurs. Nevertheless, after careful morphological examination and comparison of all allied species in the Curcuma genus, especially in subgenus Ecomata, it was found that this plant did not match any existing species. Therefore, we describe it here as a new species to science with the name of Curcuma pulcherrima, according to this species's very beautiful inflorescences and flowers. In contrast, its morphological characteristics description, illustrations, vernacular name, ecology, phenology, distribution, utilization, conservation status, map of distribution, and comparison table of the new species and its ally species, including a revised key to the species of Curcuma subgenus Ecomata are provided.